A Comparison of the Efficacy of Once-Daily Fluticasone Furoate/Vilanterole with Twice-Daily Fluticasone Propionate/Salmeterol in Elderly Asthmatics - Ishiura, Yoshihisa; Fujimura, Masaki; Shiba, Yasutaka; Ohkura, Noriyuki; Hara, Johsuke; Abo, Miki; Kasahara, Kazuo (Drug Research, 2018)
Background Asthma in the elderly population has been focused because it affects quality of life and results in a higher hospitalization rate and mortality. Fluticasone furoate (FF)/vilanterole (VI) is a novel inhaled corticosteroids (ICS)/long-acting β2 agonist (LABA) combination being developed for once-daily administration for asthma with greater anti-inflammatory activity and longer duration of bronchidilation. The ElliptaTM dry powder inhaler (DPI) has also been available as a new device with high levels of satisfaction and preference.Methods A 12-week, randomized, open-label cross-over, pilot study was conducted in 18 elderly patients with bronchial asthma to compare the effectiveness of once-daily FF/VI 200/25 µg via the ElliptaTM DPI vs. twice-daily fluticasone propionate (FP)/salmeterol (SAL) 500/50 µg via the DiskusTM DPI. The study period included a 4-week run-in, the first 4-week treatment, and the second 4-week treatment. Respiratory functions, fractional exhaled nitric oxide (FeNO) and asthma control test (ACT) scores were measured 0, 4, and 8 weeks after randomization. Preferences for their device were also assessed using a self-completed questionnaire.Results Spirometric paramters, FeNO levels and ACT scores were not significantly different during the run-in period, the FP/SAL treatment period, and the FF/VI treatment period. FF/VI treatment via the ElliptaTM DPI was preferred to the FP/SAL treatment via the DiskusTM DPI (p<0.01).Conclusions These data indicate that FF/VI treatment via the ElliptaTM DPI is preferred in elderly patients with asthma based on its ease-of-use, suggesting the potential to improve patient adherence and, as a result, overall disease management.